(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Academic and analogous intellectual output by different postcolonial critics and thinkers has led to the reformulation of the conventional and time-honoured notions about culture. This renewed interest in cultural and ethnological matters has served to redeem the discourse on diaspora from the confines of nation-state and place it within the larger global, hybrid, multicultural and multinational space. The term diaspora is pertinent in both historical and current context, as it invokes as much to the dispersal of Jews under the ire of Nebuchadnezzar as to the flight of Rohingyas from the military offences in Rakhine state. Any act of migration whether forced or voluntary, conjures diaspora sentiments. An examination of diaspora position involves the awareness of existential challenges like adaptations and modifications according to the demands of new locale, where epistemological violence might be exacted upon the subject and a new world-view developed by himher consequently. In substance, diaspora literature addresses the complexities that transpire in tandem with the simultaneous act of geographical uprooting from one place, and installation into other, faced either by any individual or group. It also provides us an insight into the transformations that any culture meets in the process of transition. Culture is then inextricably latched onto the identity of the migrant. Therefore any variation in the geographical space disturbs the cultural coordination and finally results into a mutilated identity. Formulated against this background, theorization of diaspora customarily has its extension in three dimensions. The first hypothesis deputes the identity of the migrant in the relationship which heshe has with the members of such communities that are formed by migrated subjects. The second conjecture is a further continuation of this relationship and it includes a sense of empathy, fostered not only for the diasporic members who are living in the same nation-state, but also for those living beyond the boundaries. The third postulation directs its interest towards homeland, and attempts to figure out the impact of its lateral connection. While closely reading into these dimensions and others, this research work intends to locate the crux of diaspora sentiment as well to display the prevailing contradictions.